Crowdfunding as an Innovative Method of Financing Small and Medium-sized Enterprises - Rymarczyk, Jan (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
An innovative form of financing, crowdfunding consists of raising cash online to realise charity and commercial projects. It has played a smaller role than other forms of innovative financing that do not rely on traditional intermediaries. With a relatively short history, advantages and constraints that are not well known and, in many countries, a lack of right legal regulations, confidence in its effectiveness is rare. This holds particularly in the countries of East Central Europe, including Poland, which have only gradually adopted the global economy’s instruments and innovative methods of financing. There is therefore a need to disseminate knowledge on crowdfunding and to show that it can meaningfully increase development, especially of small firms and start-ups, as a complementary and sometimes alternative source of financing. The paper uses empirical, theoretical and general logic methods to analyse the subject literature, reports from international organisations and online sources of information.